2020
DOI: 10.1088/1742-6596/1490/1/012049
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting adolescent nutritional status in Banda Aceh, Indonesia

Abstract: The purpose of this study was to examine factors affecting nutritional status, anemia status, and adolescent blood pressure in Banda Aceh, Indonesia. A cross-sectional study was designed using interviewed questionnaire on nutritional status, knowledge about nutrition, and anemia status. National Health Research Data (Riskesdas) in 2013 shows the prevalence of obesity in adolescents 13-15 years based on Body Mass Index (BMI) was 8.3% and for very fat was reaches 2.5%. Although these prevalences are still lower … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…It is an important stage of human development that determines one's health [1]. Adequacy of adolescent's nutrition will also affect the future life such as the level of intelligence [2]. A previous study reported that adolescent's nutritional status was influenced by diet, pocket money, and knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is an important stage of human development that determines one's health [1]. Adequacy of adolescent's nutrition will also affect the future life such as the level of intelligence [2]. A previous study reported that adolescent's nutritional status was influenced by diet, pocket money, and knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…A previous study reported that adolescent's nutritional status was influenced by diet, pocket money, and knowledge. One of the alternatives to increase the nutritional status of adolescents is by improving their eating patterns [2]. The other factors that can influence the adolescent's nutritional status are physical activities, body image, psychology, and gender [3].…”
Section: Introductionmentioning
confidence: 99%
“…Status gizi remaja juga ditemukan berhubungan dengan uang saku yang didapatkan. PenelitianKesuma et al (2020) menemukan bahwa uang saku menjadi faktor yang signifikan pada status gizi remaja di Banda Aceh, Indonesia.…”
unclassified